Peningkatan Penerapan Model Pembelajaran Kooperatif Siswa Dalam Pembelajaran Sosiologi Kelas XI IPS 2 SMAN 9 Maros - Devia Ananda Umar; Firdayanti J Umar; Nurafiqah. M; Sahriani Haerul; Andi Paida (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this study was to determine the learning process of improving the learning outcomes of Sociology students Class XII Social Studies 2 SMAN 9 Maros through cooperative learning and whether there was an improvement after action. At this stage, researchers prepare learning tools which will support the learning processin the classroom. In addition, observation sheets are also prepared processing with cooperative learning models, and observation sheets of teacher and student activities. From the observations made during the learning process at UPT SMAN 9 MAROS by applying the cooperative learning model or cooperative learning provides little change in students for those who follow learning in class, including: Students are motivated to learn,Students have also begun to be skilled in experimenting and practicum can also support the understanding of the subject matter, students are predominantly active in the learning process.